What is microhistory? : theory and practice - Sigurºur G. Magnússon.; Szíjártó, István. (London ; New York : Routledge, 2013)
"What is Microhistory provides the first accessible and comprehensive introduction to the origins, development, methodology and position of Microhistory"--
pt. 1. Introduction : against simple truths -- pt. 2.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Microhistory; Electronic books